1998
DOI: 10.1021/ac980573i
|View full text |Cite
|
Sign up to set email alerts
|

Method Performance and Validation for Quantitative Analysis by 1H and 31P NMR Spectroscopy. Applications to Analytical Standards and Agricultural Chemicals

Abstract: Nuclear magnetic resonance (NMR) can be used to provide an independent and intrinsically reliable determination of chemical purity. Unlike chromatography, it is possible to employ a universal reference standard as an internal standard for the majority of chemical products assayed by quantitative NMR (QNMR). This is possible because the NMR response can be made the same for all chemical components, including the internal standard, by optimizing certain instrumental parameters. Experiments were performed to vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(138 citation statements)
references
References 55 publications
5
131
0
2
Order By: Relevance
“…Maniara et al 21 reported a systematic validation of the quantitative NMR method. Their validation demonstrated that when carefully implemented, the purity of major components in a complex mixture can be determined with accuracy and precision better than 1%, and impurities comprising Ä0.1% of the sample mass can be quantified.…”
Section: Methodsmentioning
confidence: 99%
“…Maniara et al 21 reported a systematic validation of the quantitative NMR method. Their validation demonstrated that when carefully implemented, the purity of major components in a complex mixture can be determined with accuracy and precision better than 1%, and impurities comprising Ä0.1% of the sample mass can be quantified.…”
Section: Methodsmentioning
confidence: 99%
“…The usefulness of quantitative NMR for the validation of natural product reference compounds as well as theoretical aspects have been shown by Maniara and Pauli. 13,14) The developed method was applied on the quantitative analysis of five different isolated cannabinoids. A similar method has been recently described by our laboratory for the quantitative analysis of bilobalide and ginkgolides in Ginkgo biloba leaves and products.…”
mentioning
confidence: 99%
“…Considering the excellent localization properties of the LASER-FOCI sequence [24], as confirmed herein, the phantom results of the protocol compare well with other assays. Yet, the LMRS protocol is roughly three times less accurate than high-resolution, non-localized MRS assays [34,35]. Though some decrease in accuracy results from low analyte-to-reference ratios, it is primarily attributable to larger line widths and gradient-induced spectral noise, as is well known.…”
Section: Accuracymentioning
confidence: 96%
“…3 suggest that the adiabatic sequence correctly assays the voxel. With regard to concentration, the linearity of the MRS response to the number of nuclei is well documented [34,35]. The LMRS response of the protocol is the relaxation corrected analyte-to-reference ratio of the integrated intensities, S 0 .…”
Section: Linearitymentioning
confidence: 99%